Gastrointestinal symbiont diversity in wild gorilla: A comparison of bacterial and strongylid communities across multiple localities - Bethan Mason; Klara J. Petrzelkova; Jakub Kreisinger; Torsten Bohm; Barbora Cervena; Emilie Fairet; Terence Fuh; Andres Gomez; Sascha Knauf; Ulrich Maloueki; David Modry; Matthew H. Shirley; et al. (Molecular Ecology, 2022)
Western lowland gorillas ( Gorilla gorilla gorilla ) are Critically Endangered and show continued population decline. Consequently, pressure is mounting to better understand their conservation threats and ecology. Gastrointestinal symbionts, such as bacterial and eukaryotic communities, are believed to play vital roles in the physiological landscape of the host. Gorillas host a broad spectrum of eucaryotes, so called parasites, with strongylid nematodes being particularly prevalent. While these communities are partially consistent, they are also shaped by various ecological factors, such as diet or habitat type. To investigate gastrointestinal symbionts of wild western lowland gorillas, we analysed 215 faecal samples from individuals in five distinct localities across the Congo Basin, using high‐throughput sequencing techniques. We describe the gut bacterial microbiome and genetic diversity of strongylid communities, including strain‐level identification of amplicon sequence variants (ASVs). We identified strongylid ASVs from eight genera and bacterial ASVs from 20 phyla. We compared these communities across localities, with reference to varying environmental factors among populations, finding differences in alpha diversity and community compositions of both gastrointestinal components. Moreover, we also investigated covariation between strongylid nematodes and the bacterial microbiome, finding correlations between strongylid taxa and Prevotellaceae and Rikenellaceae ASVs that were consistent across multiple localities. Our research highlights the complexity of the bacterial microbiome and strongylid communities in several gorilla populations and emphasizes potential interactions between these two symbiont communities. This study provides a framework for ongoing research into strongylid nematode diversity, and their interactions with the bacterial microbiome, among great apes.

Daily defecation outputs of mountain gorillas (Gorilla beringei beringei) in the Volcanoes National Park, Rwanda - Elie Sinayitutse; David Modry; Jan Slapeta; Aisha Nyiramana; Antoine Mudakikwa; Richard Muvunyi; Winnie Eckardt (Primates, 2021)

Anaerobic Fungi in Gorilla (Gorilla gorilla gorilla) Feces: an Adaptation to a High-Fiber Diet? - Doreen Schulz; Moneeb A. Qablan; Ilona Profousova-Psenkova; Peter Vallo; Terence Fuh; David Modry; Alexander K. Piel; Fiona Stewart; Klara J. Petrzelkova; Kateřina Fliegerová (International Journal of Primatology, 2018)

MYD88 and functionally related genes are associated with multiple infections in a model population of Kenyan village dogs - Michaela Necesankova; Leona Vychodilova; Katerina Albrechtova; Lorna J. Kennedy; Jan Hlavac; Kamil Sedlak; David Modry; Eva Janova; Mirko Vyskocil; Petr Horin (Molecular Biology Reports, 2016)

Gut microbiome composition and metabolomic profiles of wild western lowland gorillas ( Gorilla gorilla gorilla ) reflect host ecology - Andres Gomez; Klara Petrzelkova; Carl J. Yeoman; Klara Vlckova; Jakub Mrázek; Ingrid Koppova; Franck Carbonero; Alexander Ulanov; David Modry; Angelique Todd; Manolito Torralba; Karen E. Nelson; et al. (Molecular Ecology, 2015)
The metabolic activities of gut microbes significantly influence host physiology; thus, characterizing the forces that modulate this micro‐ecosystem is key to understanding mammalian biology and fitness. To investigate the gut microbiome of wild primates and determine how these microbial communities respond to the host's external environment, we characterized faecal bacterial communities and, for the first time, gut metabolomes of four wild lowland gorilla groups in the Dzanga‐Sangha Protected Areas, Central African Republic. Results show that geographical range may be an important modulator of the gut microbiomes and metabolomes of these gorilla groups. Distinctions seemed to relate to feeding behaviour, implying energy harvest through increased fruit consumption or fermentation of highly fibrous foods. These observations were supported by differential abundance of metabolites and bacterial taxa associated with the metabolism of cellulose, phenolics, organic acids, simple sugars, lipids and sterols between gorillas occupying different geographical ranges. Additionally, the gut microbiomes of a gorilla group under increased anthropogenic pressure could always be distinguished from that of all other groups. By characterizing the interplay between environment, behaviour, diet and symbiotic gut microbes, we present an alternative perspective on primate ecology and on the forces that shape the gut microbiomes of wild primates from an evolutionary context.